Electrochemical nanostructuring of (111) oriented GaAs crystals: from porous structures to nanowires - Monaico, Elena I.; Monaico, Eduard V.; Ursaki, Veaceslav V.; Honnali, Shashank; Postolache, Vitalie; Leistner, Karin; Nielsch, Kornelius; Tiginyanu, Ion M. (Beilstein Journal of Nanotechnology, 2020)
A comparative study of the anodization processes occurring at the GaAs(111)A and GaAs(111)B surfaces exposed to electrochemical etching in neutral NaCl and acidic HNO3 aqueous electrolytes is performed in galvanostatic and potentiostatic anodization modes. Anodization in NaCl electrolytes was found to result in the formation of porous structures with porosity controlled either by current under the galvanostatic anodization, or by the potential under the potentiostatic anodization. Possibilities to produce multilayer porous structures are demonstrated. At the same time, one-step anodization in a HNO3 electrolyte is shown to lead to the formation of GaAs triangular shape nanowires with high aspect ratio (400 nm in diameter and 100 µm in length). The new data are compared to those previously obtained through anodizing GaAs(100) wafers in alkaline KOH electrolyte. An IR photodetector based on the GaAs nanowires is demonstrated.
Keywords: anodization; crystallographically oriented pores; gallium arsenide (GaAs); nanowires; neutral electrolyte; photocurrent; porous GaAs

(untitled) - Föll, H.; Langa, S.; Carstensen, J.; Christophersen, M.; Tiginyanu, I. M. (Adv. Mater. (Weinheim, Ger.), 2003)

(untitled) - Föll, H.; Carstensen, J.; Frey, S. (J. Nanomater., 2006)

Porous Semiconductors - Kochergin, V.; Föll, H. (Springer, 2009)

(untitled) - Tiginyanu, I.; Monaico, E.; Monaico, E. (Electrochem. Commun., 2008)

(untitled) - Tiginyanu, I. M.; Ursaki, V. V.; Monaico, E.; Enachi, M.; Sergentu, V. V.; Colibaba, G.; Nedeoglo, D. D.; Cojocaru, A.; Föll, H. (J. Nanoelectron. Optoelectron., 2011)

(untitled) - Bian, Y.; Zheng, Z.; Zhao, X.; Liu, L.; Su, Y.; Xiao, J.; Liu, J.; Zhu, J.; Zhou, T. (J. Lightwave Technol., 2013)

(untitled) - Wallentin, J.; Anttu, N.; Asoli, D.; Huffman, M.; Åberg, I.; Magnusson, M. H.; Siefer, G.; Fuss-Kailuweit, P.; Dimroth, F.; Witzigmann, B.; Xu, H. Q.; Samuelson, L.; et al. (Science, 2013)

(untitled) - Service, R. F. (Science, 2013)

(untitled) - Cui, Y.; Wang, J.; Plissard, S. R.; Cavalli, A.; Vu, T. T. T.; van Veldhoven, R. P. J.; Gao, L.; Trainor, M.; Verheijen, M. A.; Haverkort, J. E. M.; Bakkers, E. P. A. M. (Nano Lett., 2013)

(untitled) - Czaban, J. A.; Thompson, D. A.; LaPierre, R. R. (Nano Lett., 2009)

(untitled) - Wang, J.; Gudiksen, M. S.; Duan, X.; Cui, Y.; Lieber, C. M. (Science, 2001)

(untitled) - Duan, X.; Huang, Y.; Cui, Y.; Wang, J.; Lieber, C. M. (Nature, 2001)

(untitled) - Tomioka, K.; Yoshimura, M.; Fukui, T. (Nature, 2012)

(untitled) - Monaico, E.; Tiginyanu, I.; Volciuc, O.; Mehrtens, T.; Rosenauer, A.; Gutowski, J.; Nielsch, K. (Electrochem. Commun., 2014)

(untitled) - Asoh, H.; Kotaka, S.; Ono, S. (Electrochem. Commun., 2011)

(untitled) - Ono, S.; Kotaka, S.; Asoh, H. (Electrochim. Acta, 2013)

(untitled) - Li, X.; Guo, Z.; Xiao, Y.; Um, H. D.; Lee, J. H. (Electrochim. Acta, 2011)

(untitled) - Tiginyanu, I. M.; Ursaki, V. V.; Monaico, E.; Foca, E.; Föll, H. (Electrochem. Solid-State Lett., 2007)

(untitled) - Volciuc, O.; Monaico, E.; Enachi, M.; Ursaki, V. V.; Pavlidis, D.; Popa, V.; Tiginyanu, I. M. (Appl. Surf. Sci., 2010)

(untitled) - Schwab, M. J.; Han, J.; Pfefferle, L. D. (Appl. Phys. Lett., 2015)

(untitled) - Monaico, E.; Moise, C.; Mihai, G.; Ursaki, V. V.; Leistner, K.; Tiginyanu, I. M.; Enachescu, M.; Nielsch, K. (J. Electrochem. Soc., 2019)

(untitled) - Zhang, C.; Yuan, G.; Bruch, A.; Xiong, K.; Tang, H. X.; Han, J. (J. Electrochem. Soc., 2018)

(untitled) - Langa, S.; Carstensen, J.; Christophersen, M.; Steen, K.; Frey, S.; Tiginyanu, I. M.; Föll, H. (J. Electrochem. Soc., 2005)

(untitled) - Prunici, P.; Irmer, G.; Monecke, J.; Sirbu, L.; Tiginyanu, I. (Phys. Status Solidi A, 2005)

(untitled) - DeJarld, M.; Shin, J. C.; Chern, W.; Chanda, D.; Balasundaram, K.; Rogers, J. A.; Li, X. (Nano Lett., 2011)

(untitled) - Song, Y.; Oh, J. (J. Mater. Chem. A, 2014)

(untitled) - Asoh, H.; Kotaka, S.; Ono, S. (Mater. Res. Express, 2014)

(untitled) - Capizzi, M.; Emiliani, V.; Frova, A.; Sarto, F. (Phys. Rev. B, 1993)

(untitled) - Sauncy, T.; Palsule, C. P.; Holtz, M.; Gangopadhyay, S.; Massie, S. (Phys. Rev. B, 1996)

(untitled) - Yu, P. W.; Fischer, D. W.; Sizelove, J. R. (Semicond. Sci. Technol., 1992)

(untitled) - Deepak; Lakshminarayana, N. (Bull. Mater. Sci., 2001)

(untitled) - Sirkeli, V. P.; Yilmazoglu, O.; Hajo, A. S.; Nedeoglo, N. D.; Nedeoglo, D. D.; Preu, S.; Küppers, F.; Hartnagel, H. L. (Phys. Status Solidi RRL, 2018)

(untitled) - Luo, Y.; Yan, X.; Zhang, J.; Li, B.; Wu, Y.; Lu, Q.; Jin, C.; Zhang, X.; Ren, X. (Nanoscale, 2018)

(untitled) - Li, Z.; Yuan, X.; Fu, L.; Peng, K.; Wang, F.; Fu, X.; Caroff, P.; White, T. P.; Hoe Tan, H.; Jagadish, C. (Nanotechnology, 2015)

(untitled) - García Núñez, C.; Braña, A. F.; López, N.; Pau, J. L.; García, B. J. (Nanotechnology, 2020)

(untitled) - Chen, X.; Wang, D.; Wang, T.; Yang, Z.; Zou, X.; Wang, P.; Luo, W.; Li, Q.; Liao, L.; Hu, W.; Wei, Z. (ACS Appl. Mater. Interfaces, 2019)

(untitled) - Chen, H.-Y.; Chen, R.-S.; Rajan, N. K.; Chang, F.-C.; Chen, L.-C.; Chen, K.-H.; Yang, Y.-J.; Reed, M. A. (Phys. Rev. B, 2011)

(untitled) - Berger, P. R. (Proc. SPIE, 2001)